Making Products Feel Special: When Metacognitive Difficulty Enhances Evaluation - Pocheptsova, Anastasiya; Labroo, Aparna A.; Dhar, Ravi (Journal of Marketing Research, 2010)
More than 200 studies suggest that metacognitive difficulty reduces the liking of an object. In contrast to those findings, the authors demonstrate that the effects of metacognitive experiences on evaluation are sensitive to the consumption domain. In the domain of everyday goods, metacognitive difficulty reduces the attractiveness of a product by making it appear unfamiliar. However, in the context of special-occasion products, for which consumers value exclusivity, metacognitive difficulty increases the attractiveness of a product by making it appear unique or uncommon. The authors reconcile their findings with prior research by positing that the effect of metacognitive experiences on evaluation depends on the naive theory people associate with product consumption. Four studies demonstrate the proposed effect and test for the role of lay theories in the interpretation of metacognitive experiences. The authors conclude with a discussion of theoretical and marketing implications.